2015
DOI: 10.1038/emi.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

‘Supermutators’ found amongst highly levofloxacin-resistant E. coli isolates: a rapid protocol for the detection of mutation sites

Abstract: Fluoroquinolone resistance is gradually acquired through several mechanisms. In particular, chromosomal mutations in the genes encoding topoisomerases II and IV and increased expression of the multidrug efflux pump AcrAB-TolC are the most common mechanisms. In this study, multiplex polymerase chain reaction (PCR) protocols were designed for high-throughput sequencing of the quinolone resistance determining regions of topoisomerases genes (gyrA, parC and parE) and/or the expression regulation systems of multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Another genetic alteration commonly seen was a frame shift at codon 29 of AcrR regulator protein (V29fs). In the same codon, V29G was reported by others [55]. Additionally, we detected other SNPs that might be significant, but have not been reported previously in the literature (S3 Table).…”
Section: Mechanisms Of Carbapenem Resistancesupporting
confidence: 84%
See 1 more Smart Citation
“…Another genetic alteration commonly seen was a frame shift at codon 29 of AcrR regulator protein (V29fs). In the same codon, V29G was reported by others [55]. Additionally, we detected other SNPs that might be significant, but have not been reported previously in the literature (S3 Table).…”
Section: Mechanisms Of Carbapenem Resistancesupporting
confidence: 84%
“…For the rest of the strains, we reported high frequency of missense mutations in porins (OmpC and OmpF), while only one was seen in regulatory OmpR protein in one strain (OM150) (S3 Table). Regarding efflux pump, we reported already known missense mutations in AcrR (T5N), MarR (G103S, Y137H, K62R, S3N), SoxR (T38S, G74R), and SoxS (A12S) to induce overexpression of the AcrAB-TolC efflux pump and contribute to fluoroquinolones and tigecycline resistance in E. coli [50][51][52][53][54][55]. Also, we saw a A111T missense mutation in SoxR, which has unclear clinical significance, as it has been seen previously in isolates with normal expression of soxS mRNA [52,55].…”
Section: Mechanisms Of Carbapenem Resistancementioning
confidence: 99%
“…Norfloxacin MICs for most of the double mutants were greater than 1024mg/L and ciprofloxacin MICs 256mg/L. Double mutations in gyrase are thought to reduce the affinity of the gyrase-DNA complex for quinolones [ 21 ]. Sequencing of QRDR region by Namboodiri et al [ 22 ] observed that isolates with an additional gyrA substitution Asp87→Asn were resistant to both ciprofloxacin as well as nalidixic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Many clinical isolates of E . coli cells highly resistant to fluoroquinolones have been isolated and the mutations that support such a high-level resistance have been identified [ 14 , 23 26 ]. It is reasonable to imagine that in clinical settings there are a large variety of pathways to high-level resistance, not necessarily similar to what we have devised here.…”
Section: Resultsmentioning
confidence: 99%